”AXIS LIBRI” International book festival (Confluenţe Bibliologice, 2019)
The author presents information from the „AXIS LIBRI” Internationalbook festival initiated and organized by the “V. A. Urechia” County Public Library, Galaţi, Romania. The XIth Edition of June 5-9, 2019 was dedicated to The Year of the Book in Romania and the event was on the Axis Libri Alley,  there were placed 40 mobile houses, which hosted the books of Romanian and foreign publishing houses.
Keywords: book festival; publishing houses